Iron incorporation affecting the structure and boosting catalytic activity of β-Co(OH)2: exploring the reaction mechanism of ultrathin two-dimensional carbon-free Fe3O4-decorated β-Co(OH)2 nanosheets as efficient oxygen evolution electrocatalysts. Issue 15 (22nd February 2017) - Sun, Fengzhan; Li, Linbo; Wang, Guo; Lin, Yuqing
Abstract : Ultrathin two-dimensional Fe3 O4 -decorated β-Co(OH)2 nanosheets are synthesized for oxygen evolution reaction and reaction mechanism is explored by first principles calculation. Abstract : It is significantly important to develop highly active catalysts for the oxygen evolution reaction (OER) for designing various renewable energy storage and conversion devices. Herein, we report a series of ultrathin two-dimensional (2D) carbon-free Fe3 O4 -decorated β-Co(OH)2 nanosheets (Fe3 O4 /Co(OH)2 NSs) as OER electrocatalysts with different Co/Fe mole ratios from 1 to 31. It is found that the different amounts of iron incorporation into Co(OH)2 NSs affects the structure of Fe3 O4 /Co(OH)2 NSs, while the optimized incorporation boosts the electrocatalytic activity of Co(OH)2 NSs for OER, i.e. the Fe3 O4 /Co(OH)2 NSs with a Co/Fe molar ratio of 15 demonstrate superior catalytic properties with respect to the lowest overpotential and smallest Tafel slope in alkaline media. First principles calculations used for exploring mechanisms show that Fe 3+ from Fe3 O4 /Co(OH)2 NSs adsorbs water molecules more energetically favorably on the surface and would offer far more improvement of the catalytic activity compared with Fe 2+ . Combined with structure analysis and calculation results, the better catalytic activity is attributed to the ultrathin structure, high active site exposure, lower adsorption energy towards water molecules and the increased positive charge of adsorbed water molecules. This research paves a way to develop highly active and durable substitutes for noble metal OER electrocatalysts.